Níveis de homocisteína e desempenho cognitivo em uma amostra populacional de idosos da cidade do Natal-RN - Araújo, Márcio Luiz Tassino de (2009)
The imprecision of the frontier that separates those cognitive deficits inherent to the human physiological aging process from those which represent the early signs of nervous system degenerative pathologies ,very prevalent among the elderly, has brought attention to the need of studies aiming to establish clinical and/or laboratorial criteria to allow this differentiation. Elderly people living in poor and developing countries are frequently exposed to precarious socioeconomic conditions which facilitate the development of an array of pathologies which have metabolic and nutritional dysfunctions as the established or proposed etiological agents. The levels of certain micronutrients, such as the vitamins B12 and B9 (folic acid), and of some intermediary metabolites, such as homocysteine are being thought of as etiological factors and/or as biological markers of a group of alterations which affect the normal functioning of the nervous system with important reflexes upon cognitive performance. This study aims to investigate the influence of homocysteine, B12 vitamin and folic acid levels on the cognitive performance of the low income elderly population. This transversal study took place in Natal, Rio Grande do Norte State, Brazil, and involved 205 dwelling elderly people, users of the Programa de Saúde da Família, a public healthcare program, maintained by the city s health authorities. A multidimensional questionnaire was used to assess the socio-demographic aspects and the overall health and nutrition conditions. The cognitive performance was measured by the use of the Portuguese version of the Mini Mental State Exam (MMSE). The serum levels of homocysteine, B12 vitamin and folic acid were determined by chemiluminescence. The association between the socio-demographic and serum levels of Hcy, B12 vitamin and folic acid was determined by multiple linear regression. Serum levels higher than 13.5 μmol/l, indicative of hyperhomocysteinemia (HHcy), were found on 25.4% of the sample, being more prevalent in men (p<0.05). Deficitary levels of folic acid (<5ng/mol) and of B12 vitamin (<193 pg/ml) were found on 3.9% and 10.2% of the sample respectively. A negative correlation was found between cognitive performance with both age and HHcy and a positive correlation was found between cognitive performance and schooling. The isolated HHcy R2 values were an explanation to only 4% of the variance of the MMSE scores. However, when associated with schooling and age, this model explains about 25% of this association